Myanmar Political Instability: A Threat to Southeast Asia Stability - Hendra Manurung (Kajian Asia Pasifik, 2021)
This research aims to explain current Myanmar political instability due to the recent military coup d’état on February 1, 2021 led by General Senior Min Aung Hlaing follow with Aung San Suu Kyi and other pro-democracy elite leaders arrests. Domestically, up to present time, after the military coup, most Burmese supporters of Myanmar's democratization such medical doctors, teachers, traders, civilian political leaders, and university students balked and staged massive demonstrations against the military coup and demanded the return of civilian government authority by the military junta government. This research revealed that this unexpected Myanmar phenomenal political situation has impact on Southeast Asia regional security and ASEAN Unity.